Skin, hair, and nail supplements advertised on Instagram. Issue 1 (2nd January 2023) - Zamil, Dina H.; Ameri, May; Fu, Shangyi; Abughosh, Ferris M.; Katta, Rajani
Abstract: Teens and young adults increasingly utilize social media for health information. Dermatologic supplements, advertised on social media, may be pharmacologically active and risk adverse effects. Instagram was searched, and 100 posts from March 2021 were evaluated for ingredients, health claims, account verification status, and endorsements. Only 4% of posts were made by verified accounts, and 1% of posts contained a visible Supplement Facts label. The Food and Drug Administration does not regulate dietary supplements. Ingredients such as vitamin A found in posts can pose teratogenic risk. Other potentially dangerous ingredients included saw palmetto and biotin. To accurately counsel patients who may retrieve health information from Instagram, it is important for practitioners to be familiar with social media claims.